‘Below ten thousand’: An effective behavioural noise reduction strategy? - Pete Smith; John Gibbs (Journal of Perioperative Nursing)
Noise in the operating theatre environment has remained a persistent and unresolved problem1. The problem currently lacks an effective solution. In order to partially resolve this issue, the authors created a behavioural noise reduction tool called ‘Below ten thousand’.